THE BAPTISM OF A PRODIGAL SON IN MARILYNNE ROBINSON’S GILEAD - BiXia Sun (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
As a contemporary American female writer, a devout Christian, Marilynne Robinson gets her religious thoughts fully manifested in her Gilead. The novel is actually a home epistle that an aged and ailing father Ames passes to his 7-year-old innocent son, which narrates the three priesthood generations’ life changes from the Civil War to 1956 by making use of Ames’s first-person narration. However, the outsider John Ames Boughton (Jack) has been subject to diverse academic interest, which proves that he dominates an important textual place. This research makes the priest Ames’s baptism for prodigal Jack as an entry point. Ames has baptized Jack and has to reluctantly confer the name “John Ames” to Jack under the request of his bosom friend Boughton. Due to Ames’s mixed feelings (jealousy) in addition to Jack’s own diverse prodigality, Ames does not want to accept Jack at all. With the focus on the tiny difference between the religious ritual baptism and the true meaning of baptism in the novel, this research aims to put forward that the priest Ames has dilemma in conveying the Bible doctrine “love your neighbors”. However, at the end of novel, after seeing the unacceptable prodigal’s love and responsibility toward his old father, colored wife and interracial son, Ames starts to introspect his inappropriate attitude toward Jack. Under the guidance of the divine epiphany, Ames is willing to accept Jack and to give Jack the spiritual consolation. By analyzing Ames’s inner conflicts between his own “covetise” and the divine epiphany—the developmental process of Ames’s acceptance of unacceptable prodigal godson, this paper hopes to argue that the last blessing Ames gives to Jack reveals that Ames’s divine epiphany overwhelms his human nature—covetise which enables him to accept even to love the unacceptable people or unpleasant things in life so as to make faith and spiritual pursuit truly become a part of contemporary life.